Effects of Susceptibility Result Suppression on National Healthcare Safety Network Antibiotic Resistance Option Data. (October 2020) - Estes, Matthew; Ouedraogo, Youssoufou; Evans, Christopher David; Muleta, Daniel; Adre, Cullen; Keaton, Amelia; Kainer, Marion
Abstract : Background: The National Healthcare Safety Network's (NHSN) Antibiotic Resistance (AR) Option offers hospitals a way to report antibiotic resistance data from their facility's laboratory information system and create facility-specific antibiograms. Suppression of select antibiotic susceptibility results may be used by antibiotic stewardship teams to prevent unnecessary use of broad-spectrum therapies by not making those susceptibilities available to providers. To be of use, antibiograms should offer a complete picture of antibiotic resistance. We wanted to understand the impact of data suppression. Methods: A retrospective cross-sectional study was conducted including data from 2017 and 2018. The clinical susceptibility data for cefotaxime, ceftriaxone, ceftazidime, ertapenem, imipenem, and meropenem against carbapenem-resistant Enterobacteriaceae (CRE), Pseudomonas aeruginosa (CRPA), Acinetobacter baumannii (CRAB), and extended-spectrum β-lactamase–producing Enterobacteriaceae (ESBL) were collected from commercial antimicrobial susceptibility testing instruments (cASTI) in 3 Tennessee healthcare networks that also report to the NHSN AR Option. These data were linked to the NHSN data using 4 keys: date of birth, isolate collection date, pathogen, and specimen source. An isolate was defined as suppressed when susceptibility results were observed from the cASTI but not in NHSN. The proportions of suppressed results were calculated and stratified by genus, facility, and antibiotic. Results: Overall, 1, 009 isolates were matched between the NHSN AR data and the laboratory test results. Of these, 4.1% were CRAB, 23.3% were CRPA, and 72.6% were Enterobacteriaceae. In total, 4, 948 susceptibility results were available from cASTIs. Suppressed results in NHSN data were observed in 918 isolates (91.0%) and accounted for 2, 797 results (56.6%). Of the 817 isolates tested against imipenem, 18.7% were found to be suppressed. Moreover, 100%, 57.9%, and 8.6% of imipenem tests against CRAB, CRPA, and Enterobacteriaceae, respectively, were suppressed. Of the suppressed results, 38.3%, 3.6%, and 58.1% were susceptible, intermediate, and resistant respectively. Of the 363 isolates tested against meropenem, 48.2% were found to be suppressed. In addition, 12.2%, 53.0%, and 52.2% of meropenem tests against CRAB, CRPA, and Enterobacteriaceae, respectively, were suppressed. Of the suppressed results, 47.4%, 11.4%, and 41.1% were susceptible, intermediate, and resistant, respectively. Conclusions: A large proportion of isolates had at least 1 analyzed antibiotic suppressed within the NHSN AR Option. It will be important to develop and implement strategies to ensure that nonsuppressed data are available to be reported to the NHSN AR module. Funding: None Disclosures: None